Designing transparent piezoelectric metasurfaces for adaptive optics - Liao Qiao; Xiangyu Gao; Kaile Ren; Chaorui Qiu; Jinfeng Liu; Haonan Jin; Shuxiang Dong; Zhuo Xu; Fei Li (Nature Communications, 2024)
Abstract Simultaneously generating various motion modes with high strains in piezoelectric devices is highly desired for high-technology fields to achieve multi-functionalities. However, traditional approach for designing multi-degrees-of-freedom systems is to bond together several multilayer piezoelectric stacks, which generally leads to cumbersome and complicated structures. Here, we proposed a transparent piezo metasurface to achieve various types of strains in a wide frequency range. As an example, we designed a ten-unit piezo metasurface, which can produce high strains (ε 3 = 0.76%), and generate linear motions along X-, Y- and Z-axis, rotary motions around X-, Y- and Z-axis as well as coupled modes. An adaptive lens based on the proposed piezo metasurface was demonstrated. It can realize a wide range of focal length (35.82 cm ~ ∞) and effective image stabilization with relatively large displacements (5.05 μm along Y-axis) and tilt angles (44.02′ around Y-axis). This research may benefit the miniaturization and integration of multi-degrees-of-freedom systems.